Standardized data collection for multi-center clinical studies of severe malaria in African children: establishing the SMAC network. - Taylor, T; Olola, C; Valim, C; Agbenyega, T; Kremsner, P; Krishna, S; Kwiatkowski, D; Newton, C; Missinou, M; Pinder, M; Wypij, D (2006)
The Severe Malaria in African Children (SMAC) network was established to conduct mortality-based trials. Although falciparum malaria kills more than one million children each year, single centers cannot enroll enough patients to detect reductions of 20-30% in mortality rates. Our aim was to quantify and describe severe malaria across a variety of epidemiological settings so that we could design intervention studies with more precise sample size estimates. We used a standardized surveillance mechanism to capture clinical, laboratory and outcome data on all parasitemic children admitted to hospital. Between December 2000 and December 2003, 20333 patients were enrolled at five sites. The frequency of severe malaria syndromes (cerebral malaria, severe malarial anemia and acidosis) differed between sites, as did the syndrome-specific mortality rates. Intervention studies targeted at reducing mortality in one or a combination of severe malaria syndromes would require 3-4 years to complete within the existing network. These data provide more accurate estimates of the disease burden of children hospitalized for malaria in sub-Saharan Africa. Networks are required to recruit enough patients for mortality-based studies and to encompass the epidemiological diversity of malaria in sub-Saharan Africa. SMAC represents the first effort to develop this capacity.